LESSON STUDY: A MODEL FOR IMPROVING INFORMATICS ENGINEERING STUDENTS ACHIEVEMENT IN ENGLISH - Patang Hafira; PAWENANG Sri (Institut Agama Islam Negeri Palopo, 2014)
This research is done due to the result of the writers previous research about Learners Attitude and Motivation in English, PDP 2013. At the research, it was found that students attitude and motivation are positive toward English learning, but students achievement was at poor category. It shows controversy. The writer assumed that the learning process was not maximal. For that reason, in this present research, the writer had done a research which aims at improving students achievement in English. The model which is used is Lesson Study (LS), considering that FKIP Cokroaminoto Palopo University has gotten Hibah Lesson Study from Dikti, so the writer applied this model in another faculty, i.e. Faculty of Computer Technique at Informatics Engineering Study Program. The aim of the research is to find out the effectiveness of LS in improving students achievement in English. The research applied a pre-experimental method with pretest-treatment-posttest design. The population is the second semester students of Informatics Engineering Study Program of Cokroaminoto Palopo University. The samples are 40 students from the total population of 388 students. The instrument of the research is general English test for pretest and posttest. For Lesson Study, the steps which were conducted are Plan, Do, and See. SPSS calculation and some of Gays formula were used to analyze the data. Based on research result, it can be concluded that Lesson Study effectively improved Informatics Engineering students achievement in English. It can be seen from the calculation of students mean score. At pretest, students mean score is 42.3 which is at poor category, while in posttest the students mean score is 68.1 which is at fairly good category.